The four fields of leadership how people and organizations can thrive in a hyper-connected world - Goodell, Tom, 1952- (Rowman & Littlefield, 2020)
"In a world that is changing faster and with more complexity than at any other time in history, Tom Goodell explores how to make sense of it all, and how individuals and organizations can thrive in a world this complex. He taps into hot business management trends of mindfulness, simplicity science, and agile leadership along the way"--